2009
DOI: 10.1021/jf902321x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Dietary Virgin Olive Oil on Blood Pressure and Lipid Composition of Serum and Low-Density Lipoprotein in Elderly Type 2 Diabetic Subjects

Abstract: Dietary virgin olive oil may help to reduce blood pressure in hypertensive individuals, but little is known about the effect on type 2 diabetic patients. For the present study, 17 type 2 diabetic elderly subjects and 23 healthy elderly controls received a diet rich in virgin olive oil for 4 weeks. Blood pressure, biochemical parameters, low-density lipoprotein (LDL), and oxidized LDL lipids and fatty acids were measured. Systolic blood pressure was reduced after virgin olive oil consumption in both controls an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…Recent epidemiological and clinical studies have confirmed that regular consumption of EVOO within the context of the Mediterranean diet is effective in preventing and treating certain diseases related to oxidative stress, inflammation and the immune system [15][16][17][18][19]. Numerous studies have demonstrated that the beneficial effects of EVOO consumption can be ascribed to minor phenol components such as flavonoids and secoiridoids oleuropein and their hydrolysis products such as hydroxytyrosol, which has demonstrated to be dose dependently absorbed in animals and humans [20].…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiological and clinical studies have confirmed that regular consumption of EVOO within the context of the Mediterranean diet is effective in preventing and treating certain diseases related to oxidative stress, inflammation and the immune system [15][16][17][18][19]. Numerous studies have demonstrated that the beneficial effects of EVOO consumption can be ascribed to minor phenol components such as flavonoids and secoiridoids oleuropein and their hydrolysis products such as hydroxytyrosol, which has demonstrated to be dose dependently absorbed in animals and humans [20].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it is recognised as one of the best food for its capacity to prevent some pathology, such as cancer and cardiovascular diseases, and to reduce their incidence in the western population (Kontogianni et al, 2007). Numerous studies show that olive oil reduces cholesterol, lowers blood pressure and the incidence of breast cancer and inhibits platelet aggregation (Perona et al, 2009;Violante, Gerbaudo, Borretta, & Tassone, 2009). Because of the high antioxidants content, olive oil appears to reduce dramatically the oxidation of low-density lipoprotein (LDL) cholesterol, thus preventing heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…The SBP was 136 mmHg in the EVOO treated subjects vs 150 mmHg in the sunflower treated group (p < 0.01). Olive oil also reduces BP in hypertensive diabetic subjects [188] . It is the high oleic acid content in olive oil that reduces BP [180] .…”
Section: Omega-9 Fatsmentioning
confidence: 98%
“…Olive oil and MUFAs have shown consistent reductions in BP in most clinical studies in humans [178][179][180][181][182][183][184][185][186][187][188][189][190] . In one study, the SBP fell 8 mmHg (p ≤ 0.05) and the DBP fell 6 mmHg (p ≤ 0.01) in both clinic and 24 h ambulatory BP monitoring in the MUFA treated subjects compared to the PUFA treated subjects [178] .…”
Section: Omega-9 Fatsmentioning
confidence: 99%